2010
DOI: 10.1007/s00044-010-9392-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis characterization and biological evaluation of some alkoxyphthalimide derivatives of 3-(4-substituted phenyl)-6,6-diphenyl-3,3a-dihydro-2H-imidazo[2,1-b]pyrazolo[3,4-d][1,3]thiazol-7(6H)-one

Abstract: A series of 2-N-ethoxyphthalimido 3-(4-substitutedphenyl)-6,6-diphenyl-3,3a-dihydro-2H-imidazo[2,1-b] pyrazolo[3,4-d][1,3]thiazol-7(6H)-one(7a-e) and 4-(4-substituted phenyl)-2-(N-ethoxyphthalimido amino)-7,7-diphenylimidazo[2 0 ,1 0 :2,3][1,3]thiazolo[4,5-d] pyrimidin-8(7H)-one (9a-e) have been designed and synthesized starting from thiohydentoin (1). The structure of all synthesized compounds has been established by IR, 1 H NMR, 13 C NMR and mass studies. These compounds have been screened for antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Due to its structural simplicity, ease of synthesis, and potent antitumor activity, this class of molecules is widely studied to find potent anticancer agents. [11][12][13] Recently, conjugates bearing imidazo [2,1-b]thiazole scaffolds have become of interest due to their broad spectrum of pharmacological activities, such as antifungal, [14,15] antibacterial, [16][17][18] anti-inflammatory, [19] and antihypertensive properties. [20] It has been reported that they possess antitumor properties against a variety of human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its structural simplicity, ease of synthesis, and potent antitumor activity, this class of molecules is widely studied to find potent anticancer agents. [11][12][13] Recently, conjugates bearing imidazo [2,1-b]thiazole scaffolds have become of interest due to their broad spectrum of pharmacological activities, such as antifungal, [14,15] antibacterial, [16][17][18] anti-inflammatory, [19] and antihypertensive properties. [20] It has been reported that they possess antitumor properties against a variety of human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazothiazole core exhibits well-known therapeutic properties such as antitumor, [1][2][3][4] antihelminthic, [5][6] fungicide, [7][8][9] cardiotonic, [10] anti-hypertensiv, [11] anti-inflammatory, [12] antibacterial, [13][14][15][16][17][18] antiparasytic, [19] antiviral , [20] anti-oxidant [21] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Also, imidazo[1,2‐ b ]pyrazole‐type derivatives are an important class of compounds in the medicinal field, with biological applications including anticancer . On the other hand, imidazo[2,1‐ b ]thiazoles occupy a great place in medicinal chemistry because of their broad spectrum of pharmacological activities, including antitumor activities against a variety of human cancer cell lines , as well as anti‐inflammatory , antibacterial , and antifungal activities .…”
Section: Introductionmentioning
confidence: 99%